Being Songwriter and Singer Using Suno as AI Music Generator: Creating English Songs for Young Learners in Teaching Vocabularies - Fitria, Tira Nur (International Journal of Computer and Information System (IJCIS), 2025)
This research simulates the use of Suno AI (https://suno.com/) in creating English songs for young learners in teaching vocabulary. This research is descriptive qualitative. The analysis shows that Suno offers AI-driven solutions encompassing song creation, sound processing, and data analysis, known for efficiently producing lifelike songs blending vocals with instruments or entirely instrumental compositions. Teachers utilize Suno AI to create English songs aimed at teaching children vocabulary, benefiting from its user-friendly tools regardless of musical expertise. This approach enhances vocabulary acquisition in engaging classroom settings, fostering creativity and emotional connections to learning materials. Teachers can customize songs to suit students' preferences and educational needs, promoting motivation and creative skills development. Using Suno AI involves visiting their website, registering, selecting a music genre and vocabulary theme (e.g., colors, numbers), and customizing generated melodies and lyrics to accommodate varying proficiency levels. The platform supports easy song creation, editing, and sharing, facilitating effective vocabulary learning through enjoyable musical experiences integrated into daily classroom activities. This innovative use of technology supports educators in enhancing language acquisition through engaging and accessible musical content, exemplified by the creation of an English children's song titled "Colors of the Rainbow." This song vividly teaches color vocabulary through descriptive lyrics and lively melodies, complemented by a "children's lively" music style that enhances its cheerful and educational impact on young learners. With Suno AI, English teachers can assume the roles of songwriters and musicians in education by utilizing its capabilities to create engaging songs tailored for teaching basic English vocabulary. Suno AI allows teachers to organize lyrics around new words, phrases, or language concepts they aim to teach, fostering a dynamic learning experience that seamlessly integrates language acquisition with musical expression. This innovative use of technology enhances educational engagement through enjoyable and effective teaching methods.Keywords: AI Music Generator, English song, Suno AI, vocabularies